Biogenic nanosilver bearing antimicrobial and antibiofilm activities and its potential for application in agriculture and industry - Trzcińska-Wencel, Joanna; Wypij, Magdalena; Rai, Mahendra; Golińska, Patrycja (Frontiers in Microbiology, 2023)
Introduction: Due to the increasing resistance of bacteria and fungi to antimicrobials, it is necessary to search for effective alternatives to prevent and treat pathogens causing diseases in humans, animals, and plants. In this context, the mycosynthesized silver nanoparticles (AgNPs) are considered as a potential tool to combat such pathogenic microorganisms. Methods: AgNPs were synthesized from Fusarium culmorum strain JTW1 and characterized by Transmission Electron Microscopy (TEM), X-ray diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy, Nanoparticle Tracking Analysis (NTA), Dynamic Light Scattering (DLS) and Zeta potential measurement. The minimum inhibitory (MIC) and biocidal concentrations (MBC) were determined against 13 bacterial strains. Moreover, the combined effect of AgNPs with antibiotics (streptomycin, kanamycin, ampicillin, tetracycline) was also studied by determining the Fractional Inhibitory Concentration (FIC) index. The anti-biofilm activity was examined by crystal violet and fluorescein diacetate (FDA) assays. Furthermore, antifungal activity of AgNPs was evaluated against a panel of phytopathogenic fungi viz., Botrytis, Colletotrichum, Fusarium, Phoma, Sclerotinia, and an oomycetes Phytophthora by agar well-diffusion and micro-broth dilution method to evaluate the minimal AgNPs concentrations that inhibit fungal spore germination. Results: Fungal-mediated synthesis resulted in the formation of small (15.56±9.22nm), spherical and stable AgNPs with good crystallinity. FTIR spectroscopy indicated the presence of various functional groups on the surface of AgNPs. The AgNPs showed antimicrobial and antibiofilm formation activities against Gram-positive and Gram-negative bacteria. The enhanced effect of AgNPs in combination with antibiotics was confirmed against human pathogens. A high inhibitory effect on the activity of bacterial hydrolases was observed by FDA assay. AgNPs inhibited fungal growth and spore germination of Botrytis cinerea, Phoma lingam and Sclerotina sclerotiorum. Discussion: F.culmorum strain JTW1 was found to be an eco-friendly biological system for an easy, efficient and inexpensive synthesis of AgNPs. The AgNPs demonstrated remarkable antimicrobial and antibiofilm activities against a wide range of human and plant pathogenic bacteria and fungi singly and in combination with antibiotics. These AgNPs could be applied in medicine, agriculture, and food industry to control pathogens that cause numerous human diseases and crop losses. However, before using them extensive animal studies are required to evaluate the toxicity, if any.